The Potential Role of Alkaloid Extract against Phospholipase Extracted from Aspergillus Flavus in Male Rats - Hussein A. R. Abbood (Journal of Global Pharma Technology, 2016)
This article aims to evaluate the role of alkaloid extract against phospholipase toxicity. The study sample contained 20 adult albino male rats divided into four groups, where each group consists of 5 rats. The groups are categorized as follows:The group of control which received ad libidium.The infected group, which was injected with (0.05ml/per animal) phospholipase.A group injected with (0.05ml/per animal) phospholipase and treated with (0.05ug/per animal) alkaloid extract.A group injected with (0.05ml/per animal) phospholipase and treated with (0.05ug/per animal) alkaloid extract.The results show a highly significant increase (P < 0.05) in the levels of Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) in the infected group compared with the control group. Oxidative stress factor in the infected group demonstrates a significant increase (P < 0.05) in the MDA (malonedialdehyied) levels. Nevertheless, it reported a significant decrease (P < 0.05) in the glutathione (GSH) levels compared with the control group. After using alkaloid extract in the treatment, non-significant changes (P < 0.05) are found in liver functions. Furthermore, MDA and GSH report non-significant changes (P < 0.05) compared with the group of control. The study demonstrates that alkaloid extract has a potential role against phospholipase that is extracted from A. flavus in rats.Keywords: Alkaloid extract; A. flavus; liver function; MDA (malonedialdehyied); glutathione (GSH).